2023
DOI: 10.1021/acs.cgd.2c01364
|View full text |Cite
|
Sign up to set email alerts
|

Searching for Suitable Kojic Acid Coformers: From Cocrystals and Salt to Eutectics

Abstract: The possibility of obtaining cocrystals of kojic acid with organic coformers has been investigated by both computational and experimental approaches. Cocrystallization attempts have been carried out with about 50 coformers, in different stoichiometric ratios, by solution, slurry, and mechanochemical methods. Cocrystals were obtained with 3-hydroxybenzoic acid, imidazole, 4-pyridone, DABCO, and urotropine, while piperazine yielded a salt with the kojiate anion; cocrystallization with theophylline and 4-aminopyr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 73 publications
0
3
0
Order By: Relevance
“…The melting of the cocrystal at lower temperatures compared to the pure components (PZQ and SUB) can be explained by the fact that the crystal lattice and the Gibbs energy of the cocrystal are lower than those of the individual components. The decrease in the melting point and enthalpy of fusion in the cocrystal compared to praziquantel alone indicates a decrease in the thermodynamic stability and implicitly a higher solubility . From the comparison of the TG curve of the cocrystal PZQ·SUB (Figure b) with the TG curves of the initial ingredients, it was observed that the decomposition of the cocrystal occurs more slowly compared to the initial ingredients, and the mass loss is lower.…”
Section: Resultsmentioning
confidence: 98%
“…The melting of the cocrystal at lower temperatures compared to the pure components (PZQ and SUB) can be explained by the fact that the crystal lattice and the Gibbs energy of the cocrystal are lower than those of the individual components. The decrease in the melting point and enthalpy of fusion in the cocrystal compared to praziquantel alone indicates a decrease in the thermodynamic stability and implicitly a higher solubility . From the comparison of the TG curve of the cocrystal PZQ·SUB (Figure b) with the TG curves of the initial ingredients, it was observed that the decomposition of the cocrystal occurs more slowly compared to the initial ingredients, and the mass loss is lower.…”
Section: Resultsmentioning
confidence: 98%
“…The molecular structure of 5H2HM4HP was examined using P1 point group symmetry and the resulting Figures 1 and 2 showcase the optimized geometry. Crystal dimensions, a = 147.515 Å, b = 102.166 Å, c = 60.572 Å; Angles between cell axes: α = 90°, β = 114.16°, γ = 90° and Volume (V) = 1.0000 (16) Å 3 [8]. In the study, theoretical bond lengths for asymmetry units (C‐6), (O‐4) and (H‐6) were found in the range 1.353–1.498 Å, 0.965–1.431 and 0.965–1.096 (in Å) at B3LYP/6‐311++G(d,p) method.…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown to provide reliable results for a wide range of molecular systems and electronic states. This choice of functional and basis set has been extensively validated and used in similar studies in the literature [7,8], balancing computational efficiency and accuracy in predicting molecular properties [9].…”
mentioning
confidence: 99%